Analisis Hukum Penggunaan Narkotika Oleh Anak: Perspektif Kebijakan Penegakan Hukum dan Perlindungan Anak - Akbar, Haikal (Proceedings Series on Social Sciences & Humanities, 2024)
This research is motivated by an increase in the use of narcotics by minors. A child is part of a nation's society who is the future or next generation of a nation. A child has the right to receive protection from various types of threats, one of which is drugs. The negative effects of drugs are that they damage health and damage children's morals. Many criminal cases are motivated by drug abuse. In certain cases, children are not only users but also distributors. This shows that the problem of drugs among minors has entered a serious stage. There are 2 factors that influence a child to use drugs, the first is an internal factor, which is meant by internal factors, namely one's own desire or curiosity that arises to try using drugs, the second is an external factor, which is meant by external factors, namely the influence of the surrounding environment, such as the circle of friends. or because of promiscuity. The aim of this research is to find out how the regulations regulate the use of illegal drugs by minors and how they are protected.